Recommendations to Reduce Cybersickness in Virtual Reality Based on User’s Personality and Eye Health - Alfonsius Geraldi; Clara Theresia; Yansen Theopilus (School of Industrial and System Engineering, Telkom University, 2024)
The use of Virtual Reality (VR) technology is closely related to Cybersickness (CS), namely a feeling ofdizziness that arises due to differences in perception between what is felt and seen. Other research showthat personality and eye health can affect a person's perception thus affecting the level of CS felt. The studyaims to identify the relationship between personality and eye health on CS and make recommendations toreduce for gaming industries. The research was conducted with within-subject experimental design with twovariables, personality and eye health. The initial study made an experimental design which was followed bya pilot study to determine the minimum sample size for the study and improvements to the experiment.Furthermore, participant data was collected in the form of personality, eye health, completion time, andVirtual Reality Sickness Questionnaire (VRSQ) score. Data was collected from 36 participants and thenprocessed statistically. The data were tested for classical assumptions and searched for their relationship withthe two-way ANOVA. After knowing the existence of a relationship, a Post-hoc Test (Tukey's Test) wasconducted to find the most significant group. The results shows that there was a significant relationshipbetween personality and eye health on CS (P-Value < 0.05), where participants with introvert personalityand abnormal eye conditions are more vulnerable. From the results of the study, it is recommended thatsettings be made to reduce screen shakes, limit playing time, choose the right game, and do oculomotorexercises before playing.